Tetranorlabdane Diterpenoids from the Deep Sea Sediment-Derived Fungus Aspergillus wentii SD-310 - Li, Xiao-Dong; Li, Xin; Li, Xiao-Ming; Xu, Gang-Ming; Zhang, Peng; Meng, Ling-Hong; Wang, Bin-Gui (Planta Medica, 2016)
Two new tetranorlabdane diterpenoids, asperolides D (1) and E (2), along with six related known congeners (3–8), were isolated and identified from the culture extract of the deep sea sediment-derived fungus Aspergillus wentii SD-310. The structures of these compounds were established on the basis of spectroscopic interpretation, and the skeleton and absolute configurations of asperolides D (1) and E (2) were determined by X-ray crystallographic analysis. Compounds 1 and 2 were evaluated for their cytotoxic activity against seven tumor cell lines and antibacterial activity against two human and eight aquatic pathogens.
Keywords: Aspergillus wentii; Trichocomaceae; marine-derived fungus; tetranorlabdane diterpenoids; cytotoxic activity; antibacterial activity